2005
DOI: 10.1111/j.1369-7625.2005.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

The rhetoric of informed choice: perspectives from midwives on intrapartum fetal heart rate monitoring

Abstract: Objective To investigate midwivesÕ attitudes, values and beliefs on the use of intrapartum fetal monitoring.Design Qualitative, semi-structured interviews Subjects and setting Fifty-eight registered midwives in two hospitals in the North of England.Results In this paper two main themes are discussed, these are: informed choice, and the power of the midwife. Midwives favoured the application of informed choice and shared a unanimous consensus on the definition. However, the idealistic perception of informed cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Translating theory into practice is a challenge, with many midwives being supportive of IA, yet feeling powerless to go against a system favoring an interventionist approach in childbirth (Hindley & Thomson, 2005). Barriers to informed choice include a midwife's belief that technology enhanced her professional status and was of higher value than her intuitive knowledge and skills; the labor unit being too busy to have conversations about EFM; and fear of litigation (Hindley & Thomson, 2005;Lewis & Rowe, 2004).…”
Section: Informed Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Translating theory into practice is a challenge, with many midwives being supportive of IA, yet feeling powerless to go against a system favoring an interventionist approach in childbirth (Hindley & Thomson, 2005). Barriers to informed choice include a midwife's belief that technology enhanced her professional status and was of higher value than her intuitive knowledge and skills; the labor unit being too busy to have conversations about EFM; and fear of litigation (Hindley & Thomson, 2005;Lewis & Rowe, 2004).…”
Section: Informed Choicementioning
confidence: 99%
“…Although midwifery practice places value in advocating for women and babies and providing informed choice, the reality is that women in labor choose what the midwife thinks is best, which isn't always based on evidence ( Hindley & Thomson, 2005).…”
Section: Informed Choicementioning
confidence: 99%
See 1 more Smart Citation
“…Mander et al (2009) argued that providing women with choices enhances the woman's autonomy and gives her some degree of control over her childbirth experience, whilst Pitchforth et al (2009) additionally aligned choice to an individual's right of self-determination. However, the notion of choice is not clear cut, Anderson (2004) argued that women only have choice to the extent that their choice is socially acceptable to the caregiver; where information may be manipulated by midwives using 'strategic communication' (Hindley et al, 2005). Thachuk (2007) suggested that choice is a fundamental moral right, but recognised that women can be coerced and sometimes are poorly informed and therefore unable to make choices.…”
Section: Informed Choicementioning
confidence: 99%
“…She concluded that, 'informed choice is a situated and highly contingent concept enacted in irrevocably unequal social and political relations' and suggested that Changing Childbirth failed because the notion of giving women choice is 'idealistic and impractical' (Stockbill, 2007, p. 575). Moreover, the cultural environment within obstetric units where most births take place is immersed in a blame culture, based on fear of litigation, making it difficult for midwives to offer informed choice when working in a highly technological environment (Hindley et al, 2005). Additionally, women may choose the extent to which they want to process information in order to maintain a sense of balance, as information, whilst helping women in making choices, can also result in increased stress and anxiety to them (Levy, 1999a (Levy, 1999b).…”
Section: Informed Choicementioning
confidence: 99%